PEMBERDAYAAN PERAWAT MELALUI PENERAPAN MODUL ARIS UNTUK MENGURANGI KECEMASAN DAN DEPRESI PADA PASIEN PENYAKIT KRONIS - Aris Citra Wisuda; Citra Suraya; Tukimin bin Sansuwito; Ersita Ersita; Atma Deviliawati; Santi Rosalina; Heriziana Hz (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
Anxiety and depression are common psychological problems experienced by patients with chronic illnesses and may affect the recovery process. Islamic spiritual care is considered a complementary approach that can help enhance calmness and strengthen patients’ coping abilities. This community service program aimed to empower nurses through the implementation of the ARIS Module (Anxiety and Depression Reduction Through Islamic Spiritual Care) to improve their competence in providing spiritual care and to contribute to better psychological outcomes among patients. The program was conducted at Siti Khadijah Islamic Hospital Palembang from August to September 2025 and involved 35 nurses. The activities included intensive training, demonstrations, role play, and supervised clinical practice, covering therapeutic communication, guided dzikr and prayer, selected Qur’anic verses, and spiritual reflection based on the ARIS Module. Evaluation was carried out through pre–post tests and monitoring of patients’ psychological responses. The program showed improvements in nurses’ knowledge and skills in delivering more structured, empathetic, and needs-based spiritual care. The implementation of the ARIS Module also contributed to reduced anxiety and depression among patients, reflected in greater calmness, relaxation, and readiness to face illness. This program provided a positive contribution to strengthening holistic nursing care in the hospital.